Reducing implant loss rates in immediate breast reconstructions. (February 2017) - Darragh, L.; Robb, A.; Hardie, C.M.; McDonald, S.; Valand, P.; O'Donogue, J.M.
Abstract: UK best practice guidelines for oncoplastic breast reconstruction were published in 2012. Implant-based reconstruction quality indicator (QI) targets for readmission, return to theatre and implant loss rates were set at 5% by 3 months, along with guidance to achieve these targets. The aims of this study were to quantify complication rates following implant-based reconstruction before and after the implementation of the guidelines. A retrospective audit of 86 patients with 106 implants in the 12 months to June 2013 was performed, C1. Following institutional changes including reducing antibiotic usage, a prospective audit was performed on 89 patients with 105 implants to June 2014, C2. Extended follow-up of salvaged implants was also performed. Demographics were not significantly different between the two cohorts apart from smoking. Implant loss rates fell from 7.5%(C1) to 1.9%(C2), p = 0.054 but at the cost of an increase in the return to theatre rate (14.2%–18%, p > 0.05). The implant salvage rate increased from 47% in C1 to 89.5% in C2, however, 3 of the implants that were salvaged were lost in the long term giving an overall salvage rate of 82.4% in C2. While an implant loss rate of <5% at 3 months appears achievable with less antibiotic use, this was made possible by the institution of an aggressive readmission and salvage policy. We would question the QI standards for readmission and return to theatre for immediate implant-based breast reconstruction, given that our implant loss rate of 1.9% was achieved with a return to theatre rate of 18%. Highlights: Audit of performance, institution of unit protocols and change in practice can lead to improvements in implant loss rates. Return to theatre for post-operative complications is an important factor in reducing implant loss rates. A 5% return to theatre rate set by the best practice guidelines for oncoplastic breast reconstruction could be questioned.